Informe de situación fitosaritaria - Región Centro Norte de Córdoba - De Rossi, R.; Guerra, F.; Lábaque, M.; Vuletic, E.; Brücher, E.; Plazas, M. C.; Guerra, G.D. (Informe de Situación Fitosanitaria, 2019)
Ninguno